Pola Pembinaan Integritas Aparatur Sipil Negara Pada Pemerintahan Daerah Kabupaten Sitaro Sulawesi Utara - Djouhari Kansil; Piet Hein Pusung (CV. Syntax Corporation Indonesia, 2021)
The purpose of this study was to determine the quality of the integrity of the State Civil Apparatus. The research method used is qualitative. The source of research data is ASN. Data were analyzed using qualitative analysis, namely data reduction, data display and verification. The results of this study indicate that fostering integrity by the district government is planned every fiscal year. It was also found that integrity training was carried out through mental and spiritual guidance in the form of workplace discipline, spiritual development in accordance with their respective religions and beliefs, conducting education and training both pre-service training and in service training including education and leadership training in positions. Fostering honesty in tupoksi, commitment, innovative and productive excellence through assigning duties and responsibilities in the position as part of the appreciation and promotion of the position for the achievements